Online Course of the Lecturer PersonalizedTraining for Network Educational Activity - E. G. Doroshenko; L. M. Ivkina; L. B. Khegay; T. A. Yakovleva (Открытое образование (Москва))
Recently, the industry of creating online lecturer courses became very popular. However, despite their significant number, the satisfaction of the trainees of these courses is not very high. The value of online education for practicing lecturers should be associated with personalized knowledge relevant to their professional activities and the possibility of gaining work experience in a modern open educational environment. The ability to professionally carry out distributed-collective activities in teaching children in the context of mass communication and globalization of education are becoming an important component of a teacher’s digital literacy. The experience of implementing the “Mega-class” project in the context of educational clusters, organized by the Academic Department of Informatics and Information Technologies of Krasnoyarsk State Pedagogical University, made it possible to identify significant deficiencies in the lecturer’s professional training for such activities and the need for recursive professional development directly in the process of organizing Mega-lessons. At the same time, the different level of lecturers’ readiness for the network educational activities and a significant range of professional aspirations should be noted.The purpose of this study is to create and substantiate a personalized model of the online lecturer training course for the network educational activities in a digital environment using the example of the Megaclass platform.The idea of creating personalized online courses is associated with the transformation of educational content into a problem-question format for structuring course modules (inverted course). Such a restructuring of educational content makes it possible to change the learning strategy: from the paradigm of “accumulating knowledge for solving problems” to the paradigm of “solving problems by mastering the necessary knowledge”.As a result of the analysis of the types of activities and possible deficits of all participants in the educational cluster in the design and conducting mega-lessons, a model of a personalized online course for preparing lecturers for the network educational activities was proposed. On its basis, the online course “Technology for developing and conducting a Mega-lesson” was developed, consisting of modules that answer the questions: what is a Mega-lesson, how to design an effectively-target model, how to form soft-skills, how to select content, how to design an organizational and activity model of the lesson, how to select the content of the lesson, how to organize the interaction of participants, develop or search for digital resources and services, etc. Training is organized in the process of real professional activity in the design and conducting of Mega-lessons in the educational cluster conditions. The course is hosted on the platform “Electronic University Krasnoyarsk State Pedagogical University named after V.P. Astafiev”, it was tested in training school teachers in the process of preparing Mega-lessons, students of Krasnoyarsk State Pedagogical University named after V.P. Astafiev within the discipline “Methods of teaching computer science”.Conclusion. The proposed method of personalizing an online course allows you to improve its consumer qualities, significantly raise the level of student satisfaction by switching to a learning strategy “from my professional deficits to the necessary knowledge” and the possibility of choosing an individual training route. The materials of the article may be of interest to developers of online courses, as well as lecturers who want to acquire the necessary knowledge and experience in educational clusters, in particular, on the Mega-class platform.